CLUB: A Contrastive Log-ratio Upper Bound of Mutual Information - Cheng, Pengyu; Hao, Weituo; Dai, Shuyang; Liu, Jiachang; Gan, Zhe; Carin, Lawrence (ICML 2020, 2020)
Mutual information (MI) minimization has gained considerable interests in various machine learning tasks. However, estimating and minimizing MI in high-dimensional spaces remains a challenging problem, especially when only samples, rather than distribution forms, are accessible. Previous works mainly focus on MI lower bound approximation, which is not applicable to MI minimization problems. In this paper, we propose a novel Contrastive Log-ratio Upper Bound (CLUB) of mutual information. We provide a theoretical analysis of the properties of CLUB and its variational approximation. Based on this upper bound, we introduce an accelerated MI minimization training scheme, which bridges MI minimization with negative sampling. Simulation studies on Gaussian distributions show the reliable estimation ability of CLUB. Real-world MI minimization experiments, including domain adaptation and information bottleneck, further demonstrate the effectiveness of the proposed method.